Analisa Intensitas Kebisingan dengan Pendekatan Pola Sebaran Pemetaan Kebisingan di Pt. Ricry Pekanbaru - Nofirza Nofirza; Sepriantoni Sepriantoni (UIN Sultan Syarif Kasim Riau, 2015)
Rubber processing in PT. Ricry, mechanically uses equipment and machines which potentially create noises. The noise is one of the physical factor of sound that lead to bad effect for health and safety. This research aimed to show noise contour map, to find out how long the exposure time for workers and alternative opinion of the control efforts in the production area. Data collection methodology by observation with calculation method of the equivalent noise level. Data collected from 40 measurement points at production area. Result of noise contour map showed the highest level of the noise; 83 dBA – 100 dBA, which has exceeded the Upper Level Limit (ULL) Kep-51/MEN/1999. and explanation as well as the maximum time accepted by workers has exceeded Upper Level Limit (ULL). The result of contour map showed 3 different color, where the green color at boiled machine indicates safe category (it is suggeted to use earplug that reach 25-30 dBA of noise reduction), yellow and red color at breaker machine, hammermil, creaper and cutter indicates danger category (it is suggeted to use earmuff that reach 25-40 dBA of noise reduction). Therefore, it’s important for the company to do a correction to reduce the noise exposure and noise control both administrative and personal control.Keywords: equivalent noise level, noise, noise control, noise contour map